DYSTOCIA DUE TO HYDROCEPHALUS IN A BUFFALO - HONPARKHE, M; SINGH, A K; BRAR, P S; DODDAGOUDAR, V G (The Indian Journal of Animal Reproduction, 2023)
The present communication puts on a record a case of dystocia due to hydrocephalic fetus and it’s pervaginal delivery through mutational operations in buffalo.